Economic implications of the Veterinary Feed Directive final rule on conventional and antibiotic-free swine production systems - Lamoreux, Brittni (My University, 2019)
The use of antibiotics in livestock production has been a point of contention since first utilized in 1951. Since then, numerous attempts to better regulate their use have been made. On January 1, 2017, a new Veterinary Feed Directive (VFD) officially went into effect banning the use of medically-important antibiotics in animal production for the purposes of feed efficiency or growth promotion. This paper uses pre- and post-VFD enactment survey data collected from Iowa pork producers and actual financial data from the FINBIN database to predict (pre-enactment) and measure (post-enactment) the immediate economic impact the VFD had on the swine industry. An additional analysis based on previous research evaluates the impacts of changes in feed efficiency and mortality rates, two factors most prominently affected by the removal of antibiotics, on the economic bottom-line for operations. Data from the study suggests that while there were concerns that feed and veterinary costs would increase following the enactment of the VFD, minimal financial impact has been realized to this point. However, the analysis suggests that a broader window following the VFD enactment is likely to show lower profits on a per head basis due to the effects that removal of antibiotics has on key cost of production areas.
Keywords: veterinary feed directive; swine; swine production; antibiotics; RWA; VFD